Feature Human Survival in Mountains - Sh., Aminov O. (European Journal of Life Safety and Stability (2660-9630), 2021)
The article discusses some issues of survival in mountainous areas and safe movement in the mountains, general characteristics of the mountains of the Republic of Uzbekistan, taking into account weather conditions, methods and methods of survival in mountains, and also provides conclusions and suggestions to improve the effectiveness of methods of survival in mountain conditions.